Dilemmas and connections : selected essays - Taylor, Charles, 1931- (Belknap Press of Harvard University Press, 2011)
There are always more things in heaven and earth than are dreamt of in one's philosophy--and in these essays Charles Taylor turns to those things not fully imagined or avenues not wholly explored in his epochal A Secular Age. Here Taylor talks in detail about thinkers who are his allies and interlocutors, such as Iris Murdoch, Alasdair MacIntyre, Robert Brandom, and Paul Celan. He offers major contributions to social theory, expanding on the issues of nationalism, democratic exclusionism, religious mobilizations, and modernity. And he delves even more deeply into themes taken up in A Secular Age: the continuity of religion from the past into the future; the nature of the secular; the folly of hoping to live by "reason alone"; the perils of moralism. He also speculates on how irrationality emerges from the heart of rationality itself, and why violence breaks out again and again.